One-Pot Reaction To Form Hydrophosphorylated Fullerenes from C60 and Ph3–nPCln/ROH - Xin, Nana; Xie, Xiuying; Zhao, Chang-Qiu; Huang, Xianqiang; Zhang, Junhong; Du, Ji-Yuan; Yang, Jie; Ma, Chun-Lin (Synlett, 2018)
Hydrophosphorylated fullerene derivatives were readily prepared in one step by treating C60 with Ph3–nPCln (n = 1–3) and ROH (R = H, alkyl). The one-pot reaction could be performed under mild conditions with moderate to good yields. Dichlorophenylphosphine and alcohols exhibited unexpected reactivity towards C60. A possible reaction mechanism involving the formation of P(III)–OH in situ was proposed to explain the experimental results.
Keywords: one-pot reaction; hydrophosphorylation; fullerenes; alcohols; dichlorophenylphosphine